Cultural communications of the diplomatic corps as a public institution - Zakharova, Oksana (Linguistics and Culture Review, 2021)
In the 18th – early 20th centuries, state ceremonial was an integral part of the system of government of European monarchies. They played a significant role in the legitimisation of power institutions (the coronation ceremony), in the administration of foreign and domestic political, ideological and cultural functions by the state. One of the first places in the hierarchy of state ceremonials is occupied by the diplomatic ceremony, in the process of preparation and in the conduct of which the leading role belongs to the representatives of the diplomatic corps. Their activities make it possible to solve these protocol and ceremonial issues more quickly. The diplomatic corps is the collective body of heads of diplomatic missions accredited to a particular government. The relevance of the study lies in exploring the role of art in diplomatic communications, which are one of the methods of building partnerships between states. The purpose of the study is to prove that culture is an important communicative factor in the system of diplomatic relations. There are no published studies on this problem in historiography. The source database includes two groups of materials: documentary publications and archival materials.